The triumph of gold - Rist, Charles (New York : Philosophical Library, 1961)
The book examines the place of gold standard in resolving the problem in the economy and preserve a free society and human freedom through a sound money. It tries to advocate that only the discipline of the gold standard will insure sound currencies and a workable international monetary system which is essential to preserve a free world.
Translation of Défense de l'or.
Includes bibliographical footnotes and index
usc 15/09/17
Loans
Keywords: Gold